Modified team-based learning: a new delivery method for concept lectures in family medicine module - Teh Rohaila Jamil; Tong, Seng Fah; Tan, Chai Eng; Noorlaili Tohit; Norhamizah Zahari (Penerbit Universiti Kebangsaan Malaysia, 2017)
Traditional didactic lectures have the disadvantage of being non-interactive and less effective to stimulate the learning process among students. A modified team-based learning method was designed to replace the didactic method of delivery four concept lectures in family medicine module. This paper describes the implementation and student feedback regarding the new method used. The four lectures are ‘Concepts of family medicine’, ‘Communication and consultation skills’, ‘Primary care approach to chronic disease’ and ‘Introduction to palliative care’. The new method incorporated pre-learning from online materials, individual and team-based concept application tests (iCAT and tCAT) and feedback. Each session catered for groups of 50 to 55 students. Pre-learning materials were accessible to students via Schoology® learning management system. Students were required to attempt iCAT prior to the formal session. During the formal session, the students discussed the answers as a team (tCAT) and defended their answers. The other groups were allowed to challenge the answers with their own justification. The facilitator for the session would provide feedback and conclusion for the session. Students’ feedback has been very encouraging. The interactivity of the sessions was useful to facilitate better understanding of the core concepts. Discussions for each group were unique based on the students’ prior experiences and ideas, making the sessions less monotonous than didactic lectures. Only one to two facilitators were required to deliver the session to a large group of students compared to similar small group discussions. In conclusion, the modified team-based learning focusing on concept application is a more interactive and engaging teaching method. It is a sustainable and practical approach to maximise benefits of the allocated time for teaching.